"Public satisfaction with social programs in Bahraini telecoms companies"A Field Study - Khalaf, Yasmeen Abbas; AlSaqer, Layla Hassan (Journal of Humanities & Social Sciences, 2020)
The aim of this study is to measure public satisfaction with the social programs organized by Bahraini telecommunication companies and the extent of their participation and knowledge of these programs. The study also aims to determine the types of social programs applied in public Relations departments in these companies and the objectives or goals of their application. The researcher was guided by the theory of social responsibility. The study was applied to three social programs in each of the three telecommunication companies operating in the Kingdom of Bahrain: Batelco, Zain, and VIVA.The results of the study showed that one of the most important aims of implementing the social programs in the Bahraini telecommunications companies was to fulfill their social responsibility towards the society and its members, especially unprivileged ones; in addition to raising awareness and developing the community. The study also found that most of the study’s participants lacked sufficient knowledge of the social programs in the Bahraini telecommunications companies, and that the majority of them were “dissatisfied" with the level of the social programs of these companies.
Keywords: public satisfaction; social programs; Bahraini telecom companies; corporate social responsibility; public relations